Prevalence of Stony Coral Tissue Loss Disease at El Seco, a Mesophotic Reef System off Vieques Island, Puerto Rico - Williams, Stacey M.; García-Sais, Jorge; Sabater-Clavell, Jorge (Frontiers in Marine Science, 2021)
Mesophotic coral ecosystems (MCEs) are ecologically and functionally vital, as they are Essential Fish Habitats that function as refugia for corals and sponges of shallow-water reefs. Stony Coral Tissue Loss Disease (SCTLD) is a relatively new lethal coral disease, first affecting coral reefs in Florida and has now spread through most of the Caribbean. SCTLD was observed in Puerto Rico in December 2019 in Culebra Island. Since then, SCTLD has appeared along the east coast of Puerto Rico, affecting primarily shallow reefs in San Juan, Culebra and Vieques Island, and Fajardo. During late June and July 2020, four mesophotic reef habitats were surveyed at El Seco (off Vieques Island), on the southeast coast of Puerto Rico. SCTLD was observed at colonized pavement (CPRT – 23–30 m), bank coral reef (BCR – 35–40 m), patch coral reef (PCR – 36–42 m), and rhodolith (Rhodo – 40–50 m) habitats. The mean percent substrate cover by sessile-benthic categories varied significantly between habitats (PERMANOVA, p < 0.001), with a higher mean (± SE) coral cover at BCR (26.95 ± 5.60%), followed by PCR (12.88 ± 3.88%). SCTLD was detected in all habitats, but the disease prevalence was significantly higher at BCR, ranging from 9.70 to 21.13% of colonies infected (Kruskal-Wallis ANOVA, p < 0.007). Even though PCR habitats exhibited less coral cover, SCTLD prevalence was still elevated ranging from 6.66 to 15.07%. The deepest record of SCTLD at El Seco was 40.9 m. The majority (∼98%) of the corals infected with the disease were from the Orbicella complex spp. (faveolata/franksi). However, there were other infected species, such as Agaricia grahamae, A. lamarcki, Montastraea cavernosa, and Porites astreoides. As seen in the surveys conducted in 2011 and 2020, the loss of coral cover allows for the emergence of other benthic “detractors,” such as peyssonnelids, specifically Ramicrusta spp. Ramicrusta spp., an aggressive encrusting red alga known to take over available space and overgrow corals, significantly increased its substrate cover at the impacted reefs. Therefore, the severity and virulence of SCTLD will most likely have severe and long-lasting negative impacts on the coral communities at El Seco mesophotic reef system.